Do modern social media applications suffer from feature creep? : Case YouTube - Sundell, Kalle (My University, 2024)
This study was conducted to examine the prevalence of excess features in modern social media platforms. Social media companies are constantly trying to find ways to improve their product, impress their audience and keep them satisfied. A common approach for achieving this appears to be the introduction of more functionality by expanding the software’s existing feature set. If these newly introduced features are poorly adopted but remain in the software’s feature set, the software may suffer from “creeping featurism”, more commonly known as “feature creep”. The presence of feature creep may have many unwanted consequences, such as decreased user satisfaction, increased difficulty in software maintenance and performance issues. This study aims to determine whether modern social media platforms suffer from this phenomenon by using the video-sharing platform YouTube as a case example. Does YouTube suffer from feature creep? One way to find out is to ask directly from its end users. For this purpose, a survey was created. In the survey, the respondents were first asked to express their personal feelings about the platform’s current state. Then, the respondents were presented with a set of features and asked to assess how useful they found a given feature to be. After this, another set of features was presented asking to assess how often they engage with a given feature. The survey was distributed across several social media platforms and a total of 44 responses were amassed. Based on the obtained results, YouTube does not seem to suffer from feature creep in its current state despite offering quite an extensive set of features. Users were mainly happy with the user interface and the vast majority of features were at least seen as “good to have”. However, an interesting observation is that a large portion of YouTube’s features appear to remain unused by the general population. This portion is even more pronounced among those who are infrequent (non-daily) users of the platform. In addition, an interesting recurring pattern was detected. Out of the features in the presented feature sets, approximately 20% of features were seen as necessary, 50% as useful and 30% as unnecessary. It remains unclear whether this pattern applies for other social media platforms as well.
Keywords: feature creep,featuritis,feature fatigue,software bloat,social media,user experience,user interface,web applications